Analisis Penerapan Preventive Maintenance Terhadap Peningkatan Produktivitas Produksi - Ahmad Jibril; Dimas Bayu Sasongko; Warkianto Widjaja; Irma Hakim; Didit Hadayanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to analyze the effect of implementing preventive maintenance on increasing production productivity in a fish canning company in East Java. This study uses a quantitative method, namely the method used to examine certain populations or samples with data collection techniques carried out through observation and the results of questionnaire answers that have been filled out by employees in the production and engineering departments. The population used in this study is the production machines used to carry out the production process with the samples used, namely production machines of 30 units. Data analysis in this study used SPSS software by conducting hypothesis testing which consisted of a coefficient of determination test (R-square) and a partial t test. Based on the results of the analysis of the calculation of the hypothesis, the t-count value of 10,624 is greater than the t-table value, which is 1,701 and the significance value obtained is less than 0.05, which means that the application of preventive maintenance on production machines has a positive and significant effect on increasing production productivity, while the R-square value obtained is 0.885 which states that the variable of applying preventive maintenance has an effect on increasing production productivity by 88.50% and the remaining 11.50% is influenced by other variables.